E-166 Utilization of radial access in neuroendovascular cases: a single-center experience. (4th August 2020) - Dakay, K; Kaur, G; Santarelli, J; Gandhi, C; Al-Mufti, F
Abstract : Introduction: Transradial access is increasingly utilized as an alternative to transfemoral access for neuroendovascular procedures; the radial approach has been widely used for cardiac catheterizations and has been shown to have a lower rate of access site complications and overall complications as compared to femoral access. However, there is a steep learning curve with institution of the transradial method including changes in patient positioning, use of the Simmons catheter, and nursing familiarity with closure devices which can often impact the adoption of this method. We demonstrate our single-center experience with widespread adoption of the transradial approach. Materials and Methods: We prospectively collected data from all neuroendovascular cases from October 2019 – February 2020 including site of approach, type of procedure, and crossover rate. We dichotomized procedures into diagnostic and interventional procedures, and further divided by the type of intervention. All interventional cases were performed via proximal radial access with a 6 French Terumo slender sheath, and either a Benchmark or Infinity guide catheter depending on the vessel of interest, patient anatomy and other features. Diagnostic cases were performed with a 5 French Terumo slender sheath and a 5 French Glide Simmons catheter; distal radial access was used in most diagnostic cases unless anatomical difficulty precluded this approach. Closure devices were used to achieve hemostasis in all patients. A spasmolytic cocktail consisting of lidocaine, nitroglycerin, and verapamil was administered in all cases; heparin was added to the cocktail unless otherwise contraindicated. For distal radial access, the Merit distal radial band was applied and kept in place with 5–10 mL of air for two hours prior to deflation. For proximal radial access, the Terumo TR band was utilized with up to 20 mL of air inflated, and kept in place for four hours prior to deflation. Results: A total of 387 cases were performed from October 2019 to January 2020, of which 94 were attempted via radial access. 4 cases were excluded due to transfemoral crossover due to patient anatomy, and 90 cases were successfully performed with radial access, for a total crossover rate of 4.3%. The use of radial access as a proportion of total case volume increased from 10.3% in October 2019 to 38.9% in February 2020 (table 1 ). A total of 20 radial interventional procedures were performed during the time period studied including flow diversion, middle meningeal artery embolization, epistaxis embolization, coiling, and thrombectomy. Conclusion: Our single-center series demonstrates low crossover rates from transradial to transfemoral of 4.3%, and shows that widespread adoption of this method can be successfully achieved in a period of a few months. Although radial access presents its own challenges, it is feasible to perform many diverse neuroendovascular cases by this route. Disclosures: K. Dakay: None. G. Kaur: None. J. Santarelli: None. C. Gandhi: None. F. Al-Mufti: None.